Genotyping of field isolates of Mycobacterium bovis and Mycobacterium tuberculosis using mycobacterial interspersed repetitive units (MIRUs) - P, RAMANE SANGRAM; VERMA, RISHENDRA; MONDAL, TISTA (The Indian Journal of Animal Sciences, 2013)
The study explored the usefulness of MIRU-VNTR genotyping in analyzing field strains of Mycobacterium bovis and M. tuberculosis. The MIRU-VNTR typing of 24 M. bovis strains with one reference strain resulted in 8 different profiles. While the MIRU-VNTR typing of 49 M. tuberculosis strains with 2 reference strains resulted in 16 different clusters. For M. bovis, HGD index varied from 0 to 0.18 in which, MIRU 2, 20, 24, 31 and 39 were mostly conserved while MIRU 4, 23 and 27 were moderately discriminatory, and none of the loci was highly discriminatory. HGD index for all loci were varied from 0 to 0.35 for M. tuberculosis strains with MIRU 39 as most discriminatory locus followed by MIRU26 and MIRU40.